Pemberdayaan Guru Mata Pelajaran Pendidikan Agama Islam Pada Kompetensi Profesional Dalam Kegiatan Ekstrakurikuler Di SDN 2 Temurejo Kab. Grobogan - Mahmud, Prof. Dr. Bambang Sumardjoko, Dr. Sumardi, M.Si (2015)
The objectives of this study areto describe: 1) professionalism competence of islamic education teacher, 2) implementation of extracurricular activities as a way to improve the professional competence of islamic education teachers, 3) factors that facilitate and constraint in the implementation of extracurricular activities as a way to enhance the professional competence of Islamic teacher teachers in SDN 2 Temurejo District of Grobogan. This research is qualitative research with case study design. Data was collected by observation, interview, and documentation. Data analysis consists of three components: data reduction, data display, and drawing conclusions or verification. Results of this research there are that: 1) Professionalism competence of Islamic education teacher have education background are elementary school, Islamic Junior High School, Islamic Senior High School and Islamic Education High School, have Islamic calligraphy writing skill and Quran recitation, master the subject matter of Islamic Religion, master the skill of deliver lectures and Strong-willed to give the competencies of Quran recitation and Islamic calligraphy writing skill. 2) Implementation of extracurricular activities as a way to empowering the professional competence of Islamic education teacher includes extracurricular of Islamic calligraphy writing, Quran recitation, Islamic Javanesse Poetry and Islamic speech conducted after the hours of rest and outside school hours. Learning process of MTQ or Quran recitation extracurricular, assisted by Islamic teacher from the outside while the calligraphy writing skills are handled directly by Islamic teacher. 3) Factors that facilitate the implementation of extracurricular activities as a way to enhance the professional competence of Islamic education teachers are support from students, parents and the policy of the school to oblige extracurricular activities of Islamic calligraphy, Tilawatil Qur'an, Islamic Javanesse Poetry, and Islamic speech. Problems were found in the implementation of extracurricular activities, namely the lack of facilities, lack of books support materials and limited funds. Keywords: empowerment, professional competence, Islamic education teacher, extracurricular